Community Development in India - Ministry of Information and Broadcasting (Ministry of Information and Broadcasting, 1958)
The basic idea underlying the National Extension movement— viz., intensive development aiming at reaching every family in the countryside and at securing co-ordinated development of rural life as a whole—is not a new concept. It has been tried in the past. One can refer to such efforts as those of the constructive workers trained by Mahatma Gandhi, or Poet Tagore at Sriniketan, or Mr. Spencer Hatch of Y.M.C.A. at Martandam, or the rural reconstruction scheme of the former Baroda State, or the experiments conducted by Mr. F. L. Brayne in Gurgaon District in the Punjab, or, in more recent times, the Sarvodaya scheme in Bombay and the Firka Development scheme in Madras.
Ministry of Information and Broadcasting
Ministry of Information and Broadcasting